2020
DOI: 10.1007/s00296-020-04663-9
|View full text |Cite
|
Sign up to set email alerts
|

Does immunosuppressive treatment entail an additional risk for children with rheumatic diseases? A survey-based study in the era of COVID-19

Abstract: The aim of the research was to further extend current knowledge of whether severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) disease 2019 (COVID-19) entails a risk for children with various rheumatic diseases under immunosuppressive treatment. Telephone survey was administered by conducting interviews with the parents from May 1, 2020 to May 20, 2020. A message containing a link to the actual questionnaire was sent to their phones simultaneously. The medical records of the patients were reviewed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 49 publications
2
33
0
2
Order By: Relevance
“…This finding that indicates the increased need for rheumatologists during the COVID-19 pandemic may be attributable to two factors: (a) patients with a rheumatic disease and/or receiving immunosuppressive treatments wanted to consult rheumatologists on their disease/treatments [30]; (b) patients consult rheumatologists on properties of several anti-inflammatory and immunomodulatory drugs that are being used in the treatment of COVID-19 because rheumatologists are experts in the use of these drugs [1,7]. Rheumatic patients may be at a higher risk of receiving COVID infection with worse outcomes, as many of them tend to be susceptible from their underlying rheumatic disease or immunocompromised due to their treatment [9][10][11][12][13][14][15][16]. Thus, this pandemic has put great responsibility on the shoulders of the rheumatologists for caring for this vulnerable patient group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding that indicates the increased need for rheumatologists during the COVID-19 pandemic may be attributable to two factors: (a) patients with a rheumatic disease and/or receiving immunosuppressive treatments wanted to consult rheumatologists on their disease/treatments [30]; (b) patients consult rheumatologists on properties of several anti-inflammatory and immunomodulatory drugs that are being used in the treatment of COVID-19 because rheumatologists are experts in the use of these drugs [1,7]. Rheumatic patients may be at a higher risk of receiving COVID infection with worse outcomes, as many of them tend to be susceptible from their underlying rheumatic disease or immunocompromised due to their treatment [9][10][11][12][13][14][15][16]. Thus, this pandemic has put great responsibility on the shoulders of the rheumatologists for caring for this vulnerable patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Since rheumatologists have substantial knowledge in the benefits and adverse effects of these drugs as well, rheumatologists are playing a significant role in this pandemic. Besides fighting COVID-19, the rheumatologists also have an essential role in caring for their rheumatic patients who may express concerns about their potential increased risk of acquiring COVID-19 infection due to their underlying disease itself and any immunosuppressive treatments they may be on [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, records in which significant influencing factors for the severity or fatality are shown, but which are not called risk factors in the title or abstract, cannot be identified by the search strategy. An example of this is [53]. It must be assumed that other risk factors for serious and fatal injuries and publications on them exist which are not covered in this review.…”
Section: Disease Specific Laboratory Valuesmentioning
confidence: 99%
“…Recently, Koker et al (14) have conducted an interesting study to examine whether the immunosuppressive treatment entails an additional risk for children with rheumatic disorder. The authors found that although some circumstances such as social distancing policy and self-isolation could influence the patients' outcomes, but treatment with immunosuppressive agents does not add an additional risk in terms of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that although some circumstances such as social distancing policy and self-isolation could influence the patients' outcomes, but treatment with immunosuppressive agents does not add an additional risk in terms of COVID-19. They concluded that, the abrupt discontinuation of rheumatic medicines could exacerbate underlying diseases and worsen the outcomes (14).…”
Section: Discussionmentioning
confidence: 99%